Image Processing Techniques-based fire detection - Ahmad, Awa Ali; Osman, Osman Sharif (Sulaimani Journal for Engineering Sciences, 2021)
In this paper different fire detection systems and techniques has been reviewed, many techniques have been developed for the purpose of early fire detection in different scenarios. The most accurate technique used among all these methods is Image Processing based Techniques. Different color models like RGB, HSI, CIE L*a*b and YCbCr have been used along with different edge detection algorithms like Sobel and Novel edge detection, finally the color segmentation technique was discussed in the review paper. All the mentioned methods in these papers have significantly proved to detect fire and flame edges in digital images with a timely manner, which has a huge impact on saving life and reducing loss of life.
Keywords: Fire detection; Image processing; Color model; Edge detection; Image segmentation